EMOTIONAL BURNING OUT OF THE ARMED FORCES OF UKRAINE PERSONNEL AS A CHALLENGE TO MENTAL HEALTH PROBLEMS IN WAR CONDITIONS - Smirnova, T. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The article is devoted to the problems of emotional burnout and excessive professional stress of the Armed Forces of Ukraine personnel in special conditions. Various concepts of emotional burnout are considered. The role and place of excessive professional stress (distress) as a predictor of the development of emotional burnout and other persistent negative manifestations are reflected. The results of a psychological study of military law enforcement officers performing duties in the area of the Joint Forces operation for signs of emotional burnout were analyzed. The general features of the course of phases and symptoms of emotional burnout in servicemen of the permanent staff of the area of the Joint Forces operation (according to the method of diagnosing the level of professional burnout, developed by V. Boyko) are determined. It is noted that the severity and phenomenology of occupational stress is individual in nature, depending on the characteristics of emotional, volitional and personal spheres, individual experience, stress and personal coping mechanisms, and working conditions. The factors of development of emotional burnout in military law enforcement officers during service in special conditions at the present stage are analyzed. Factors of professional activity associated with excessive stress contribute to the development of emotional burnout and is one of the factors in the turnover of professional staff from the Armed Forces of Ukraine. The way to prevent the development of emotional burnout in the early stages can be comprehensive prevention, which will include optimization of external conditions and control of the regime, self-regulation of mental and physical activity, positive interaction in the team. Also, the prospects of further research raised the issue of restoring the mental and physical health of the serviceman’s personality after prolonged exposure to traumatic factors and burnout. At the moment, one of the ways out in the deep stages of this process is to change the profession, but this can contradict the vital meanings of the individual and as a result cause a deep personal crisis. When dismissing servicemen, it is advisable to consider more carefully the reasons for dismissal, use other opportunities to retain a specialist in the professional activity by choosing the strategy of career building and redistribution of functions that suit them.